Boosted electromagnetic wave absorption performance from multiple loss mechanisms in flower-like Cu9S5/RGO composites. (15th June 2021) - Liao, Jun; Ye, Mingquan; Han, Aijun; Guo, Jianming; Liu, Qingzhong; Yu, Gaoqiang
Abstract: Electromagnetic (EM) wave absorber with the characteristics of thin thickness, strong absorption capacity and broad absorption bandwidth is desirable to address the EM radiation. In this work, the flower-like Cu9 S5 /RGO (CSR) composites were synthesized via a solvothermal method. Various kinds of characterizations were utilized to certify the successful preparation and properties of CSR composites. To explore the EM wave absorption performance of the CSR composites, we measured the EM parameters and calculated the reflection loss (RL) values of all the samples. Owing to the comprehensive effect of well impedance matching and large attenuation constant, the CSR-2 sample exhibited the minimum RL value of −51.9 dB at the thickness of 2.8 mm, and the widest effective absorption bandwidth (EAB) is 3.92 GHz in 1.5 mm. Furthermore, the absorption mechanisms were revealed, the impressive EM wave absorption performance of the CSR-2 is inseparable from the conductive loss and polarization relaxation, as well as the slight magnetic loss. We consider that the CSR composite can be a promising candidate for efficient and superior EM wave absorption absorber. Graphical abstract: Image 1 Highlights: The flower-like structure of Cu9 S5 /RGO composites were synthesized via a facile method. The samples with 20 wt% loading present optimal EM wave absorption properties. The sample possesses the minimum RL value of −51.9 dB at a thin thickness of 2.8 mm. An efficient and lightweight EM wave absorber with low filler loading is obtained. The absorption mechanisms are revealed.